Implementasi Sistem Informasi Akademik Menerapkan Metode Rapid Application Development - Anggun Fergina; Alun Sujjada; Fadillah Alviqih (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
A web-based Academic Information System (SISFO) has been developed using the RAD (Rapid Application Development) method to increase efficiency in managing academic data. This SISFO includes various important features such as student data management, class schedules, student attendance, and grade management. With easy access for administrators, teachers and students, this system allows them to quickly and efficiently obtain the academic information they need. It is hoped that the implementation of this SISFO will make a significant contribution in increasing the efficiency of education management as well as provide significant benefits for all parties involved. This research has succeeded in developing a web-based Academic Information System using the RAD (Rapid Application Development) method. The developed system includes important features such as student data management, class schedules, student attendance, and grade management. In this system, users such as administrators, teachers, and students can easily access and obtain the required academic information. Implementation of this system is expected to increase efficiency in education management and provide significant benefits for all users involved in the education process